KAJIAN STILISTIKA DALAM NOVEL SANG PEMIMPI KARYA ANDREA HIRATA (THE STUDY OF STYLISTICS IN SANG PEMIMPI NOVEL WRITTEN BY ANDREA HIRATA) - Susiana Herliati (Universitas Lambung Mangkurat, 2018)
AbstractThe Study of Stylistics in Sang Pemimpi Novel Written by Andrea Hirata. The study of stylists in thenovel of Sang Pemimpi of Andrea Hirata presents an excellent story about young business to achievedreams but still adheres to traditions and religions with all the “juvenile delinquency of the world”, aswell as the hard work of achieving dreams that have been declared. How is the use of figurative languagein the novel Sang Pemimpi by Andrea Hirata which includes: (1) figurative speeches for comparison,(2) figurative speeches for conflicts, (3) figurative speeches for relationships, (4) figurative speeches forrepetition and how the imagery contained in the novel Sang Pemimpi Andrea Hirata which includes: (1)visual imagery, (2) auditory imagery, (3) kinesthetic imagery, (4) motion imagery, (5) olfactory imagery,(6) gustatory imagery, (7) experiences related to nature 8) the souls related to the senses. This research usesdescriptive method. The reason for using this method because based on its characteristics, this methodis oriented to the effort of obtaining information about certain phenomena systematically, factually andaccurately based on the facts obtained from the object of study. Descriptive method is a problem-solvingprocedure that is done by describing or describing the state of the object of research based on existingfacts. Thus, the results of the above research have two topics that have not been achieved because theresults are not there as in figurative language or style of language as in the case of contradictions that iseksimoron or style of language that use the word opposite the word is not found, as well as on the imageryof the novel The Dreamer also did not find the results of the data, while the other data has a number ofdifferent according to the results found in the novel text of the leader of Andrea Hirata’s work.Key words: stylistics, figure of speech, imageryAbstrakKajian Stilistika dalam Novel Sang Pemimpi Karya Andrea Hirata. Kajian stilistika dalam novel SangPemimpi Karya Andrea Hirata memaparkan cerita yang sangat baik tentang usaha muda untuk meraihmimpi tetapi tetap menaati tradisi dan agama dengan segala “kenakalan dunia remaja”, sekaligus kerjakeras meraih mimpi yang telah dicanangkan. Bagaimanakah penggunaan bahasa figuratif dalam novelSang Pemimpi karya Andrea Hirata yang meliputi: (1) majas perbandingan, (2) majas pertentangan, (3)majas pertautan, (4) majas perulangan dan Bagaimanakah citraan (imagery) yang terdapat dalam novelSang Pemimpi karya Andrea Hirata yang meliputi: (1) citraan penglihatan, (2) citraan pendengaran,(3) citraan rabaan, (4) citraan gerak, (5) citraan penciuman, (6) Pencecapan, (7) Pengalaman berkaitandengan alam, dan (8) jiwa berkaitan dengan indera. Penelitian ini menggunakan metode deskriptif.Adapun alasan menggunakan metode ini karena berdasarkan karakteristiknya, metode ini berorientasi93pada upaya pemerolehan informasi tentang fenomena-fenomena tertentu secara sistematis, faktual,dan akurat berdasarkan fakta yang didapat dari objek kajian. Metode deskriptif merupakan prosedurpemecahan masalah yang dilakukan dengan menggambarkan atau mendeskripsikan keadaan objekpenelitian berdasarkan fakta-fakta yang ada. Dengan demikian, hasil penelitian di atas tersebut adadua topik yang belum dicapai karena hasilnya tidak ada seperti pada bahasa figuratif atau gaya bahasaseperti pada majas pertentangan yaitu aksimoron atau gaya bahasa yang mempergunakan kata yangberlawanan kata tidak ditemukan, begitu pula pada pencitraan pencecapan pada novel Sang Pemimpijuga tidak ditemukan hasil data tersebut, sedangkan data yang lainnya memiliki jumlah yang berbedabedasesuai dengan hasil yang ditemukan pada teks novel Sang Pemimpin karya Andrea Hirata tersebut.Kata-kata kunci: stilistika, majas, citraan